Pengaruh Kualitas Produk Terhadap Kepuasan Konsumen Toko Amira Meubel Kota Gorontalo - Fandriananto Sayedi; Rosman Ilato; Radia Hafid; Usman Moonti; Sudirman Sudirman (Journal of Economic and Business Education, 2023)
The present research aimed to determine the effect of product quality on customer satisfaction at Amira Furniture Store, Gorontalo City.This research employed a quantitative approach with a survey research method. The data used were primary data obtained from disributing questionnaires to customers of Amira Furniture Store, Gorontalo City, with a sample of 40 respondents. In the meantime, the data analysis technique used simple linear regression.In conclusion, product quality had a significant effect on customer satisfaction at the Amira Furniture Store, Gorontalo City. In addition, product quality effectively and efficiently had a significant effect on customer satisfaction for 51.4%, while the remaining 48.6% were affected by other variables examined in this research. This result signified that product quality significantly affected customer satisfaction at Amira Furniture Store, Gorontalo City.